Native PAGE to study the interaction between the oncosuppressor p53 and its protein ligands. Issue 4 (2nd January 2015) - Lamberti, Anna; Sgammato, Roberta; Desiderio, Doriana; Punzo, Chiara; Raimo, Gennaro; Novellino, Ettore; Carotenuto, Alfonso; Masullo, Mariorosario
<x xml:space="preserve">Abstract</x> In the present study, we investigated a new approach for studying the interaction between p53 and MDM2/X (where MDM is murine double minute protein). The method is based on the different mobility between the interacting domains of the oncosuppressor p53 and its protein ligands MDM2/X on polyacrylamide gels under native conditions. While the two proteins MDM2/X alone were able to enter the gel, the formation of a binary complex between p53 and MDM2/X prevented the gel entry. The novel technique is reliable for determining the different affinity elicited by MDM2 or MDMX toward p53, and can be useful for analyzing the dissociation power exerted by other molecules on the p53–MDM2/X complex.